Descripción de una nueva especie de Ornithotrema Caballero, Brenes & Arroyo, 1963 y creación de una nueva sub-fam¡lia de Microphallidae Travassos, 1921 (Trematoda, Digenea) - Caballero y C., Eduardo (1964)
Omithotrema longibursatus n. sp. is described, differing from O. momoti Caballero, Brenes , Arroyo, 1963, by the following characters: l.-Shape of the body. 2. Presence of a very thin, wea acetabulum or ventral sucker. 3.-Morphology of the digestive system. 4.-Size of the cirrhus pouch. 5.-Form of the testes and ovar). 6.-Development and position of the uterus. 7.-Shapc and distribution of the vitelline glands. The characters of the excretory system, observed in the present specimens, lcad the authors to place the genus in the family Microphallidr Travassos, 1921, within which it would constitute a new subfamily Ornithotrematinae n. subf. The generic diagnosis is amended to include the presence of a non-muscular ventral acetabulum.